The Effect of Fertilization and Irrigation on Maize(Zea mays L.) Production - Megyes, Attila; Rátonyi, Tamás; Huzsvai, László (Acta Agraria Debreceniensis, 2003)
In a long-term field experiment set up at the Látókép experimental station of the Center of Agricultural Sciences of Debrecen University, the data of the last five years (1995-1999) were analyzed to determine the crop production factors with the greatest influence on maize production and the relationship and interactions between irrigation and fertilization.In the extremely dry year of 1995, fertilization was found to cause substantial yield depression in the absence of irrigation. According to results of analysis of variance, fertilization significantly reduced the maize yield by 40-90% compared to control plots. Under irrigated conditions, there was a considerable increase in the maize yield, the yield surplus being 4.4-9.4 t ha-1, depending on the nutrient supply level.During the period from 1996-1999, when rainfall conditions were favorable for maize, fertilization significantly increased the maize yield even without irrigation over the average of the four years. The yield surplus due to fertilization was 3.9-4.6 t ha-1, depending on the fertilization rates. The maximum yield surplus was obtained on plots fertilized with 120 N kg ha-1, while at the rate of 240 N kg ha-1 the maize yield did not differ significantly from this value. During the period examined, corn yield was significantly higher at all three nutrient supply levels as the result of irrigation than in the non-irrigated treatment. As in the case of non-irrigated conditions, the highest fertilizer dose did not result in a substantial yield increase. An analysis of the interaction between fertilization and irrigation indicated that the yield-increasing effect of fertilization was not significantly different under irrigated and non-irrigated conditions. The significant year x irrigation interaction was confirmed by the fact that the yield surplus (1.3-2.3 t ha-1) differed greatly from the irrigation effect recorded in 1995.